2017
DOI: 10.1097/dss.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intra-arterial and Subcutaneous Testicular Hyaluronidase Injection Treatments and the Vascular Complications of Hyaluronic Acid Filler

Abstract: A complete enzymatic degradation of HA filler to hyaluronidase needs a certain time, and subcutaneous hyaluronidase treatment may be the better option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 37 publications
0
33
0
2
Order By: Relevance
“…They demonstrated that subcutaneous hyaluronidase injection showed better recovery of blood perfusion with development of less tissue necrosis than direct intra‐arterial injection. Studies of changes in the vascular structures was not done so it is not known if endothelial damage from intra‐arterial hyaluronidase could have been the cause of the better results from subcutaneous injection …”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that subcutaneous hyaluronidase injection showed better recovery of blood perfusion with development of less tissue necrosis than direct intra‐arterial injection. Studies of changes in the vascular structures was not done so it is not known if endothelial damage from intra‐arterial hyaluronidase could have been the cause of the better results from subcutaneous injection …”
Section: Discussionmentioning
confidence: 99%
“…However, the correct method for managing necrosis due to embolism or compression after HA injection is still controversial in the field. Hyaluronidase treatment is always accomplished with subcutaneous diffusion into the tissues affected by ischemia (Wang et al, ). Some studies have suggested that it is not necessary to administer hyaluronidase directly into the blood vessels, because its administration by diffusion appears to be effective (Kim et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly established that, in the case of HA accumulation, the injection of hyaluronidase next to the filler can be performed in a safe and easy way (Moraes Ferraz, Sandkvist, & Lundgren, ). When perivascular compression occurs, HA accumulation can be felt by clinical palpation, and hyaluronidase can be easily and directly injected next to the accumulation (Chang et al, ; Wang et al, ). To simulate this clinical scenario, we directly soaked an HA filler bolus in hyaluronidase solution in a test tube.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations